Kegiatan Produksi dan Usaha Meminimasi Waste di PT Coats Rejo Indonesia Menggunakan Metode Lean Manufacturing - Dari, Siska Wulan; Sulistyowati, Enik (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract In the manufacturing industry, machine efficiency is a key factor in increasing productivity and reducing operational costs. This study aims to improve the efficiency of the industrial yarn production process at PT. Coats Rejo Indonesia. This company is a manufacturer of high-quality industrial yarn. This study uses an integrated approach between the Waste Assessment Model (WAM) and Value Stream Analysis Tools (VALSAT) to identify and reduce waste in the production process. The goal is to provide recommendations for improvements that can improve the efficiency and competitiveness of the company. The research methods used include direct observation at the production site, interviews with related parties, data analysis, and the application of WAM and VALSAT. The results of the study indicate that the main type of waste identified is Rework. This information will be used to develop appropriate strategies to reduce Rework and improve overall production efficiency.